Suicide attempts among alcohol-dependent pain patients before and after an inpatient hospitalization. (1st June 2016) - Ashrafioun, Lisham; Kane, Cathleen; Stephens, Brady; Britton, Peter C.; Conner, Kenneth R.
Highlights: In alcohol-dependent veterans, examined association of pain and suicide attempts. Pain is associated with attempts prior to inpatient hospitalizations. Pain no longer associated after controlling for psychiatric disorders. Pain does not appear to offer additional risk in already high-risk population. Abstract: Background: This study examined (1) whether pain diagnoses were risk factors for non-fatal suicide attempts before and after inpatient hospitalizations in alcohol-dependent veterans, and (2) the characteristics of pain patients who attempted suicide. Method: Administrative data from the Veterans Health Administration were used to identify veterans with an alcohol use disorder who had an inpatient hospitalization during fiscal year 2011 (n = 13, 047). Logistic regression analyses were used to examine the associations of suicide attempts before and after hospitalizations with pain diagnoses, demographics, medical comorbidity, and psychiatric comorbidity. Results: Bivariate analyses and analyses controlling for demographics and medical comorbidity, indicated that pain diagnoses were significantly associated with suicide attempts in the 365 days before hospitalization (Odds RatioAdjusted [OR] = 1.22). This effect was not significant after controlling for psychiatric disorders. Pain diagnoses were not identified as risk factors of suicide attempts in the 365 days following discharge. Subgroup analyses among only those with a pain diagnosis revealed that being younger (OR = 2.64), being female (OR = 2.28), and having an attempt in the year prior to hospitalization (OR = 4.11) were risk factors of suicide attempts in the year following hospitalization. Additionally, younger age (OR = 2.13) and depression (OR = 3.53) were associated with attempts in the year prior to the hospitalization. Conclusions: This study suggests that psychiatric disorders account for the relationship between pain diagnoses and past suicide attempts among hospitalized alcohol-dependent veterans. Pain-specific suicide prevention efforts may be better targeted at less intensive levels of care.